Character, Xanthone Content and Antioxidant Properties of Mangosteen Fruit’s Hull (Garcinia mangostana L.) at Several Fruit Growth Stadia - Ani Kurniawati (Indonesia Society of Agronomy (PERAGI) and Department of Agronomy and Horticulture, Faculty of Agriculture, IPB University, Bogor, Indonesia, 2011)
The objective of this study was to evaluate the characteristics of mangosteen fruit’s hull, xanthone content, and antioxidant potential on various stadia of mangosteen fruit development. The experiment was conducted in September 2006 until July 2008 using randomized complete block design, with three replications at maturation stage i.e. 1, 2, 3, and 4 months after anthesis. The parameters being observed were fruit’s hull characters, xanthone content, and antioxidant capacity. The results of this study showed that fruit diameter and fruit weight increased until three months after anthesis and then did not change signifi cantly once they entered the process of maturity. Thickness of fruit’s hull differed signifi cantly among maturation stage. The thickness of fruit hull was observed at two months and the highest weight was at three months after anthesis. Xanthone content of mangosteen fruit’s hull at a month up to four months after anthesis did not differ signifi cantly however capacity of antioxidant differed signifi cantly among fruit ages, the IC50 values increased with the increase of fruit maturation. Keywords: Antioxidant, fruit growth, fruit’s hull, mangosteen, xanthone